Peningkatan kemampuan penggunaan ejaan dan tanda baca pada menulis karangan sederhana melalui metode complete sentence pada peserta didik kelas iii sekolah dasar - Wisnu Adji Aditya Pradana; Rukayah Rukayah; Hadiyah Hadiyah (Universitas Sebelas Maret, 2019)
Abstract: The research purposed to increase the students ability especially in understanding of using spelling and punctuation on students class III SD Negeri Tegalsari No 60 Surakarta by complete sentence method and to describe the learning process with the method was proven able to increase the students ability of using spelling and punctuation in writing simple essay on students class II SD Negeri Tegalsari No 60 Surakarta Student Year 2018/2019. The subject of this research was students class III SD Negeri Tegalsari No 60 Surakarta. They were amounts 23 students. The form of this research was Classroom Action Research within somecycles. The data was collected by test and observation. The test was used to measure the ability of using spelling and punctuation and the observation was used to measure teacher perform and student activity. The data was also analysed by using interactive data analysis. The result showed that complete sentence mehtod was proven able to improve the ability of using spelling and punctuatuion in writing simple essay on students class III SD Negeri Tegalsari No 60 Surakarta. It was proven by the grade average in the first cycle and second cycle always improved. The first cylce was only 13 (56,51%) from 23 students who passed the minimum ≥ 66. The highest grade was 88, the lowest grade was 40, and the grade average was≥66 in the first cycle. In the second cyle, the grade increased. Amounts 16 students (78,267%) could pass the test and get grade ≥66. The highest grade was 90, the lowest grade was 58, and the grade average was 73,28 in the second cycle.Keywords: Complete Sentence Method, The Cognitive Ability in understanding of using spelling and punctuation, elementary school